Enhancing point-of-care testing through standardized training and redeployment of pharmacy technicians in the community setting - Sarah Pope; Hunter Hill; Lindsey Cardosi; Lindsey Henson; Mike Wasson; Sara Stallworth; Kim Ward; Shane P. Desselle; Kenneth C. Hohmeier (Elsevier, 2021)
Objectives: The primary objective of this study was to assess the impact of a standardized training model for technician-supported point-of-care testing (POCT) on the number of health screenings performed across two states in a large community chain pharmacy. Secondary objectives included the assessment of pharmacist and technician perceptions of advanced roles of the pharmacy technician in POCT service delivery. Practice description: Certified pharmacy technicians (CPhTs) across six regional divisions of a large community chain pharmacy in Tennessee and Ohio participated in a standardized training program prior to implementation of technician-supported POCT. Practice innovation: Standardized training consisted of pre-training assessments, online training modules, post-training assessments, followed by in-person skills-based assessments. CPhT participation was limited to technical tasks of POCT (e.g. sample collections, quality assurance). Evaluation methods: The study addressed its primary objective by comparing total number of health screenings for included pharmacies in 2019 as compared to 2020. Descriptive and inferential statistics were used. Perceptions were assessed using an electronic, Likert-type scale questionnaire. Results: Pharmacies with technician-supported POCT showed a 46% increase in the total number of health screenings performed vs. 2019. The survey found that 74% (106/144) of pharmacists and 83% (34/41) of CPhTs agreed or strongly agreed that technician-supported POCT is acceptable for their practice site. Most pharmacy personnel agreed or strongly agreed that the service was appropriate and feasible for their respective practice sites. Conclusion: This study provided supporting evidence that technician-supported POCT may positively impact the number of health screenings conducted in a community pharmacy setting. Standardization of training may allow for expansion of this service across additional states. Furthermore, pharmacy personnel perceptions were overall positive.